Insuficiencia respiratoria aguda en paciente masculino de 73 años con antecedente de cirrosis hepática. - Hurtado Romero, Grace Pierina (2020)
The respiratory function is the gaseous exchange of oxygen and carbon dioxide which implies a perfect balance and control between the components of the respiratory system, therefore it is essential to learn to quickly recognize the circumstances that produced it as well as the symptoms and signs that we find in these patients in this way will be the ability to presume rapid diagnosis and appropriate initial care immediately applying basic and advanced support measures efficiently to patients with respiratory failure, it is for this reason that the following clinical case is presented , evaluating each disease presented and each treatment used in the patient, as well as the medication necessary to prioritize the patient's health and improve their quality of life and health status.